Conductivity performance evaluation of fractures filled with proppant of different sizes in shale with LBM-DEM. (4th February 2020) - Zuo, Hong; Deng, Shouchun; Huang, Zhenghong; Xiao, Chengxu; Zeng, Yongqing; Jiang, Jinlin
This paper proposes a coupled discrete element method (DEM) and lattice Boltzmann method (LBM) to compute the conductivity of fractures filled with proppant in shale as a function of the closure pressure. The particle discrete element was applied to model proppant-shale interaction process under variable closure stress, and the pore-scale simulation was carried out by LBM to model gas flow in the reconstructed digitised model (the deformed proppant-filled fractures). The laboratory bench-scale experiments were conducted in support of the numerical modeling examining the proppant embedment into the shale as a function of closure stress and measuring the conductivity of proppant-filled fractures as the proppant embedment experiments were conducted under different axial load conditions. The numerical results calculated by LBM-DEM were validated by a calibration test and the laboratory bench-scale experiments, and an agreement was achieved between them, indicating the effectiveness of this proposed method. [Received: June 28, 2017; Accepted: February 1, 2018].